Anti-capitalist satirical attitude in novels by Sonallah Ibrahim and Martin Amis - Alkodimi, Khaled Abkar (2011)
This study examines the satirical attitude of Sonallah Ibrahim and Martin Amis in the selected literary texts. Taking Ibrahim and Amis as authors who bitterly criticised the established socioeconomic conditions of the late twentieth century society, the analysis centers on two novels each, whose satirical tone, together with their subject matter and wide spread popularity, make them essential reading in this context. The study argues that Ibrahim and Amis have employed the mode of satire to mock the idea that capitalism works for the welfare of societies and individuals. The study relies on Leonard Feinberg and Gilbert Highet’s views of satire as well as on the definitions of Northrop Frey and Mtumane among others to analyse Ibrahim and Amis’ use of satiric devices suc as exaggeration, irony and distortion to express their anti-capitalist stance as presented in the selected novels. While Frey views satire as an “attitude”, Mtumane stresses the significance of the literary devices used, such as above, to express such attitude. The study shows that the two authors have used satire as a vehicle to expose the monstrous nature of the capitalist system that hides its hegemony and exploitation behind the mask of ideology. To this end, their satiric exposition grotesquely shows that consumerism is but a form of exploitation, promoted by capitalism for its own survival. Besides, the study also shows that Ibrahim and Amis have critically presented capitalist society as a class-ridden one that is characterised by inequality and oppression for poor people, and how those people are mechanically driven to search for false success in afree market economy. In this sense, the study makes use of Marxist perspectives on capitalism to further highlight Ibrahim and Amis’s satirical views on capitalism as an exploitative and oppressive social system. Finally, this thesis stresses the power of satire as a subversive weapon against hegemonic culture and the power of global capitalism which Ibrahim, as a Third World writer in particular, has uniquely employed in his work. The concluding comments show that satirists almost emerge out of their social contexts. Ibrahim and Amis are but voices of resistance for the socioeconomic unjust embodied in the capitalist system that transformed societies into markets, individuals into consumers and workers into machines. They utilised certain satirical devices to ridicule the social unjust that appears to be a significant characteristic of both societies. This leads me to further conclude that Ibrahim and Amis’ novels are significant satiric fictions employed as a means to enlighten the public of the negative impact of capitalism on societies.